TINJAUAN KESIAPAN IMPLEMENTASI REKAM MEDIS ELEKTRONIK DI PUSKESMAS KLAMPIS - Nurul Fitrian, Audinar; Ferdianto, Angga (JURNAL MEDICAL P-ISSN : 2685-7960 e-ISSN : 2685-7979, 2023)
Based on Republic of Indonesia Government Regulation Number 24 of 2022 concerning Medical Records, it is explained that every health service facility is required to maintain electronic medical records no later than December 31, 2023. At the Klampis Health Center, they still use manual medical records, but are planning to switch to electronic medical records. The purpose of study is to identify readiness for implementation. Electronic medical records at the Klampis Health Center. The method used in this research was quantitative descriptive. The population of this study were all officers at the Klampis Health Center who were involved in using and filling in medical records. Sampling method used a total sampling technique with a total of 60 respondents. Based on the analysis results in terms of the DOQ - IT method, the human resources aspect was in the very ready category with an average value of 4.11. In terms of organizational work culture was in the very ready category with an average score of 4.14. In the governance aspect, leadership was in the very ready category with an average score of 4.13. The IT infrastructure aspect was in the very ready category with an average value of 4.09. Using medical records will be easier by harmonizing technology such as electronic medical records. Health workers must be able to balance their competencies during the transition period. The implementation of EMR will speed up and facilitate information accessibility